Comparison of Stock Price Risk Measurement of BUMN Banks - Muslimin Muslimin (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Currently, most people around the world suffered and has changing the ways of their lives. This resulted in a slowdown in global economic growth in 2020. This also affected stock markets in Indonesia in almost all sectors. In addition, the stock market performance of the financial industry was also significantly affected, including state-owned banks. This study aims to analyze the potential loss from investing in the stock market of the state bank for the next 15 days by reviewing the risk value as a tool to measure the maximum loss. The findings show that Autoregressive AR(1)-GARCH(1) is suitable for determining the models mean and variance, which are used to calculate the Value at risk (VaR) of each bank. The VaR measurement for all banks shows a negative sign indicating the investor's maximum loss from holding one of the shares of that bank for the projected period of time. Measurement of risk will be one of the things that investors will consider when investing in financial markets.